A compact triband patch antenna design at terahertz frequencies - Youssef Amraoui; Imane Halkhams; Rachid El Alami; Mohammed Ouazzani Jamil; Hassan Qjidaa (Universitas Ahmad Dahlan, 2025)
The rapid evolution of terahertz (THz) technology has fueled an increasing demand for efficient, compact, and adaptable antennas that can function for a number of frequency bands in the THz spectral regime. This research outlines the analyses and design process of a multiband antenna for THz applications. Initially, an antenna with a single frequency band is created without any slot, with its lower resonant mode functions at a singular frequency of 171 GHz. To achieve multiband functionality, various rectangular slots can be added into the microstrip antenna’s radiating element. The suggested structure is constructed on a polyimide substrate, while its radiating elements are crafted from copper, with a compact size of 1.4×1.1×0.14 mm. It can achieve a reflection coefficient of −30.38 dB, −33.37 dB, and −19.33 dB at 123 GHz, 168 GHz, and 182 GHz, respectively. Furthermore, the antenna yields favorable gains at the respective frequencies, measuring 3.97 dB, 4.34 dB, and 5.66 dB for 0.123, 0.168, and 0.182 THz respectively. Additionally, the antenna demonstrates high efficiencies of 81.5%, 85%, and 91.2%, respectively. Hence, the suggested THz antenna will be useful for surveillance radar (123 GHz), medical imaging (168 GHz), and radio astronomy (182 GHz) applications.